2007
DOI: 10.1111/j.1365-2850.2007.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

The recovery alliance theory of mental health nursing

Abstract: The recovery alliance theory (RAT) is a mid-range theory of mental health nursing based on humanistic philosophy. The conception of the RAT was the outcome of collaboration among service users, practising mental health nurses, educationalists and managers and was developed in the context of a number of political and social changes as well as changes in the mental health field. The theory is composed of six constructs: humanistic philosophy, recovery, partnership relation, strengths focus, empowerment and commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 56 publications
1
42
0
8
Order By: Relevance
“…From this perspective, there is an increasing alignment of mental health care to the principles of personal recovery (Shanley & Jubb-Shanley, 2007); led by service users rather than professionals (Slade et al, 2017), and which promotes the development of a new sense of self in the presence or absence of symptoms (Deegan, 1996;Anthony, 1993). This could justify the role of collaborative sporting participation from a theoretical perspective since it could play a part in social integration, and personal recovery.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…From this perspective, there is an increasing alignment of mental health care to the principles of personal recovery (Shanley & Jubb-Shanley, 2007); led by service users rather than professionals (Slade et al, 2017), and which promotes the development of a new sense of self in the presence or absence of symptoms (Deegan, 1996;Anthony, 1993). This could justify the role of collaborative sporting participation from a theoretical perspective since it could play a part in social integration, and personal recovery.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…De estos constructos El modelo Tidal subraya la importancia de las historias personales del paciente mental y la utilización de su propia voz se derivan tres conceptos: afrontamiento, alianza de trabajo y autorresponsabilidad y control, que forman la base para un sistema de cuidados llamado Partnership in Coping. La construcción de esta teoría se ha inspirado en la preocupación por los derechos humanos, los avances en la autonomía del paciente, la atención comunitaria, el enfoque de la recuperación y la atención centrada en la persona 20 .…”
Section: Modelos De Recuperaciónunclassified
“…Care that instead focuses on recovery and self-care emphasises the individual in a holistic way (Lucock et al 2011). Research has shown that patients with psychiatric problems require insight into their illness, which promotes the ability to perform self-care (Shanley & Jubb-Shanley 2007). Psychiatric symptoms constitute barriers to self-care (El-mallakh 2006), and, therefore, an understanding of and insight into the diagnosis is of great importance.…”
Section: Self-carementioning
confidence: 99%